PRIMARY ANTIBODY TITERS AGAINST STREPTOCOCCUS SUIS IN WHITE RATS VACCINATED WTH DIFFERENT ADJUVANTS - Pramesti, Pipit Dwi; Mahardika, I Gusti Ngurah Kade; Besung, I Nengah Kerta (Buletin Veteriner Udayana, 2022)
Streptococcus suis is a gram-positive bacterium causing various diseases in pigs and a zoonosis pathogen. Therefore, an effective vaccine for S . suis is crucial to reduce the economic loss due to this pathogen. Most of the inactivated vaccines required additional substances to help increase the vaccine’s efficacy in inducing antibody titers using adjuvant.  The study aimed to know the difference of primary antibody titer of inactivated S. suis vaccine with different adjuvant addition. The adjuvant employed was water in oil (w/o) Montanide ISA 78 VG , water in oil in water (w/o/w) Montanide ISA 201 VG , and gel Montanide 01 PR. The test animals were white rats intramuscularly (IM) vaccinated under a 0.5 ml dosage. Blood sampling was conducted in week-1, -2, and -3 post-vaccination. Then, the blood serum was tested using the ELISA test. Quantitative results of ELISA were observed from the optical density (OD) value measured using the ELISA reader. The results show a significant difference in the OD value with a significance value of 0.001 (P<0.01). The best antibody response was indicated by the highest OD value. Vaccine with adjuvant w/o has the highest OD value i.e. 0,175, when compared with adjuvant gel i.e. 0,143, and adjuvant w/o/w i.e 0,103.